One Mandarin Benefits the Whole Clan: Hometown Infrastructure and Nepotism in an Autocracy - NGUYEN, Kieu-Trang (Institutional Knowledge at Singapore Management University, 2012)
This paper studies nepotism by government officials in an authoritarian regime. We collect a unique dataset of political promotions of officials in Vietnam and estimate their impact on public infrastructure in their hometowns. We find strong positive effects on several outcomes, some with lags, including roads to villages, marketplaces, clean water access, preschools, irrigation, and local radio broadcasters, as well as the hometown’s propensity to benefit from the State’s “poor commune support program”. Nepotism is not limited to only top-level officials, pervasive even among those without direct authority over hometown budgets, stronger when the hometown chairperson’s and promoted official’s ages are closer, and where provincial leadership has more discretionary power in shaping policies, suggesting that nepotism works through informal channels based on specific political power and environment. Contrary to pork barrel politics in democratic parliaments, members of the Vietnamese legislative body have little influence on infrastructure investments for their hometowns. Given the top-down nature of political promotions, officials arguably do not help their tiny communes in exchange for political support. Consistent with that, officials favor only their home commune and ignore their home district, which could offer larger political support. These findings suggest that nepotism is motivated by officials’ social preferences directed towards their related circles, and signals an additional form of corruption that may prevail in developing countries with low transparency.